Mechanism Analysis of Current--Voltage Characteristic in a Lightly Doped Drain Polycrystalline Silicon Thin-Film Transistor Using Activation Energy - Kimura, Mutsumi; Nakashima, Akihiro (Japanese Journal of Applied Physics, 2012)
We have analyzed the mechanism of the current--voltage characteristic in a lightly doped drain (LDD) polycrystalline silicon (poly-Si) thin-film transistor (TFT) by investigating the activation energy ($E_{\text{a}}$) in an experiment and the energy band calculated using device simulation. In the off state, $E_{\text{a}}$ decreases as the gate voltage ($V_{\text{gs}}$) and drain voltage ($V_{\text{ds}}$) increase, which suggests that the off-leakage current is subject to phonon-assisted tunneling with the Poole--Frenkel effect at the junction between the LDD and drain regions. In the subthreshold state, $E_{\text{a}}$ sharply decreases as $V_{\text{gs}}$ increases, which suggests that the subthreshold-transition current is subject to the potential barriers at the junctions between the source, LDD, and channel regions. In the on state, $E_{\text{a}}$ gradually decreases as $V_{\text{ds}}$ increases, which suggests that the on current is subject to the potential barriers at the grain boundaries.